Art Outside the Lines : New Perspectives on GDR Art Culture - Kelly, Elaine (German Monitor, 2011)
This collection of essays, written by leading scholars in the fields of East German art, film, literature, music, and museum studies, seeks to renegotiate the artistic legacy of the German Democratic Republic. Combining a range of theoretical and practical perspectives, the volume challenges the narrow frameworks of totalitarianism and Ostalgie that have dominated discussions of art produced in the GDR. It explores the diversity of art produced in the state and contests the long-held perception that socialist realism and artistic innovation were mutually exclusive. Crucially, the collection puts art itself to the fore; GDR art is considered not simply as a political by-product, as is so often the case, but as an entity of innovation and aesthetic value in its own right